Development of sol-gel-derived Ti0² thin films as pH-sensitive electrodes for EGFET-based soil pH sensor. - Zulkefle, Muhammad Al Hadi (2025)
pH measurement is one of the most important parameters in a wide range of applications. Conventional glass-based pH electrodes are fragile and require internal electrolyte to operate, limiting its usage in soil's pH detection. In contrast, extended gate field effect transistor (EGFET) pH sensor does not suffer from these drawbacks and is more flexible in terms of sensing electrode (SE) or sensing membrane selection. The performance of the EGFET pH sensor would be highly dependent on the SE chosen. Compared to other pH-sensitive materials, titanium dioxide (T1O2) is compelling considering its low cost, abundance, and ease of fabrication. Common fabrication methods for Ti02 include sputtering and thermal chemical vapor deposition (TCVD) which require high vacuum and high temperature, respectively. On the other hand, the sol-gel-based method does not need high vacuum or high temperature during deposition, making the process easier and lower in cost. The focus of this study is to investigate a suitable sol-gel-based fabrication technique for the production of Ti02 thin film as pH-sensitive electrode for EGFET pH sensor.